Analisis Skala Ekonomi, Efisiensi Input, dan Pendapatan Usahatani Jagung Manis (Zea Mays Saccarata Sturt) di Desa Nario Indah Kecamatan Wawotobi Kabupaten Konawe - Bayu Pratama; Suharjo Suharjo; Sarty Syarbiah (Pusat Riset dan Inovasi Nasional, 2024)
Corn is one of the most important commodities in, Konawe Regency Southeast Sulawasi. Corn is included in the strategic food group whose demand continues to increase every year. Even though corn production in Southeast Sulawasi, Konawe Regency continues to increase, it cannot meet demand, which ultimately forces the government to import corn. This research was carried out in Nario Indah Village, Wawotobi District, Konawe Regency. The population of this study consisted of 25 people. The sample was taken by census as many as 25 people. The aim of this research is to analyze the economic scale, revenue, costs and income as well as the efficiency of production inputs in sweet corn farming in Nario Indah Village, Wawotobi District, Konawe Regency. The research results show that the economic scale of sweet corn farming in Nario Indah Village, Wawotobi District, Konawe Regency is in a condition of Increasing Return to Scale. Receipts amounting to Rp. 19,982,820/ Ha, cost of Rp. 9,779,086/Ha, and the income from sweet corn farming in Nario Indah Village, Wawotobi District, Konawe Regency is Rp. 10,203,734/Ha. The production inputs for land area, labor, herbicides show that they are inefficient, while the production inputs for seeds, urea and insecticides show that they are not efficient in sweet corn farming in Nario Indah Village, Wawotobi District, Konawe Regency.